Assessing environmental education through KBSM social sciences subjects: Three case studies - Chong S.T.; Ng Y.J.; Loh K.S.; Abd Rahman A.Z. (Mattingley Publishing, 2023)
Behavioral research; Curricula; Disaster prevention; Disasters; Education; Losses; Textbooks; Content analysis; Disaster preparedness; Disaster risk reductions; Environmental education; KBSM; Malaysia; Secondary schools; Social well-being; Floods